Massage effleurage dan petrissage virgin coconut oil (VCO) menurunkan risiko gangguan integritas kulit pada pasien stroke - Djamaludin, Djunizar; Chrisanto, Eka Yudha; Risnarita, Desi (JOURNAL OF Public Health Concerns, 2024)
Background: Impaired skin integrity is the most common nursing problem in stroke patients who experience prolonged bed rest. This condition causes infection, pain and psychological impacts. Nursing interventions prevent damage to skin integrity in stroke patients, one of which is by applying massage effleurage and petrissage virgin coconut oil (VCO). Purpose: To determine the implementation of nursing care between two stroke patients using the application of massage effleurage and petrissage virgin coconut oil (VCO). Method: Descriptive research with a case study approach regarding nursing care using massage effleurage and petrissage virgin coconut oil (VCO) on the risk of skin integrity disorders in stroke patients in the neurology room at Dr. H. Abdul Moeloek hospital Lampung Province in 2024. The instrument used was a medical surgical nursing care format sheet in the form of a pressure ulcer risk observation sheet using the Braden scale. Results: The use of VCO effleurage and petrissage massage can help reduce the risk of skin/tissue integrity disorders by improving skin health and moisture. The results of implementation for the two clients showed slight differences in the results of the Braden scale. This happened because when the implementation was carried out, client 1 started actively changing sleeping positions on the right/left side every 2 hours on the 2nd day, while client 2 started being active on the 3rd day. Conclusion: Nursing care carried out by providing massage effleurage and petrissage VCO nursing actions can reduce the risk of skin/tissue integrity disorders in stroke patients.   Keywords: Effleurage And Petrissage Massage Using Virgin Coconut Oil (VCO); Risk of Skin/Tissue Integrity Disorders; Stroke.   Pendahuluan: Gangguan integritas kulit menjadi masalah keperawatan yang paling sering terjadi pada pasien stroke yang mengalami tirah baring lama. Kondisi ini mengakibatkan terjadinya infeksi, rasa nyeri, dan dampak psiokologis. Intervensi keperawatan mencegah kerusakan integritas kulit pada pasien stroke, salah satunya dengan penerapan massage effleurage dan petrissage virgin coconut oil (VCO). Tujuan: Untuk mengetahui implementasi asuhan keperawatan antara kedua pasien stroke menggunakan penerapan massage effleurage dan petrissage virgin coconut oil (VCO) Metode: Penelitian deskriptif dengan pendekatan studi kasus mengenai asuhan keperawatan penerapan massage effleurage dan petrissage virgin coconut oil (VCO) terhadap risiko gangguan integritas kulit pada pasien stroke di Ruang Neurologi RSUD Dr. H. Abdul Moeloek Provinsi Lampung Tahun 2024. Instrumen yang digunakan adalah lembar format asuhan keperawatan medikal bedah berupa lembar observasi risiko dekubitus menggunakan skala Braden. Hasil: Penggunaan massage effleurage dan petrissage VCO dapat membantu menurunkan risiko gangguan integritas kulit/jaringan dengan meningkatkan kesehatan dan kelembapan kulit. Hasil implementasi pada ke 2 klien didapatkan sedikit perbedaan hasil skala Braden. Hal tersebut terjadi karena pada saat implementasi dilakukan, klien 1 mulai aktif mengubah posisi tidur miring kanan/kiri setiap 2 jam pada saat hari ke-2, sedangkan pada klien 2 mulai aktif pada hari ke-3. Simpulan: Asuhan keperawatan yang dilakukan dengan memberikan tindakan keperawatan massage effleurage dan petrissage VCO dapat menurunkan risiko gangguan integritas kulit/jaringan pada pasien stroke.   Kata Kunci: Massage Effleurage; Petrissage Virgin Coconut Oil (VCO); Risiko Gangguan Integritas Kulit/Jaringan; Stroke.